Public policy for efficient education - Walter H. Fisher; Christian Keuschnigg (Institute for Advanced Studies (IHS), 2000)
This paper studies the role of public policy to promote efficiency in human capital accumulation in the representative agent framework. Agents accumulate human capital by spending time in home study and in publicly provided schools. The individual faces an aggregate externality in the accumulation of skills. In addition, the return to time spent in school is subject to congestion. To correct these distortions, a tuition fee combined with personal stipends is required, which shifts education in schools and universities to noninstitutional forms of learning such as home study. The dynamic effects of shifts in education policy as well as their welfare implications are also calculated in the paper.
Keywords: H21; H42; I21; I28; 330; education; human capital accumulation; optimal policy; Humankapital; Bildungsinvestition; Bildungsökonomik; Prinzipal-Agent-Theorie; Theorie